2020
DOI: 10.1186/s12939-020-01230-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care for Black and Latina women living with HIV in the U.S.: a qualitative study

Abstract: Background: Ending the HIV epidemic requires that women living with HIV (WLWH) have access to structurally competent HIV-related and other health care. WLWH may not regularly engage in care due to inadequate quality; however, women's perspectives on the quality of care they receive are understudied. Methods: We conducted 12 focus groups and three in-depth interviews with Black (90%) and Latina (11%) WLWH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 41 publications
0
35
0
1
Order By: Relevance
“…Specifically, social and structural barriers prevent women from accessing and accepting HIV care and treatment services [ 18 ], and achieving viral suppression and adhering to ART [ 19 ]. Additionally, these social and structural factors contribute to suboptimal quality of care and reduce the quality of life for women living with HIV [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, social and structural barriers prevent women from accessing and accepting HIV care and treatment services [ 18 ], and achieving viral suppression and adhering to ART [ 19 ]. Additionally, these social and structural factors contribute to suboptimal quality of care and reduce the quality of life for women living with HIV [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…HIV stigma may delay or deter women from accessing prevention and treatment services, and thus contribute to greater susceptibility to HIV infection and transmission, and suboptimal care and support for people living with HIV/AIDS (PLWHA) [ 24 ]. Women living with HIV report fears and experiences of HIV-related stigma in health care settings as a hinderance to engagement in HIV care [ 21 ]. HIV-related stigma may also hinder one’s ability to disclose their HIV status and prevent women from seeking social support [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…30 Threats to autonomy include paternalism, which manifest in systems (eg, political, economic, health care) that restrict people's choices. Examples of paternalism in health care settings experienced and reported by WLWH have taken the form of minimal support for and advice regarding pregnancy, 31,32 overestimation of HIV transmission risks to infants, 25 and lack of patient centeredness, 19 all of which can be interpreted as systematic disrespect for the reproductive choices and moral agency of WLWH. Despite minimal risk of maternal-to-child transmission of HIV, recent work by Hill and colleagues highlights that WLWH are more likely than women without HIV to undergo tubal ligations to eliminate vertical HIV transmission risks.…”
Section: Reproductive Autonomymentioning
confidence: 99%
“…11 This medicalization of reproduction is magnified for BWLWH, who account for the largest share of HIV diagnoses among women 12 and are at increased risk of adverse health outcomes (ie, lower antiretroviral treatment adherence and higher morbidity and mortality) 13,14,15 due to disparities in health care access, social inequities (eg, violence, competing life demands), 10 intersecting stigmas (eg, gender, race, class, and health status), 16,17,18 and dissatisfaction with their treatment by health care clinicians. 19 Contemporary models of care promote informed, autonomous reproductive decision making for WLWH, given the relatively low risk of maternal-to-child (perinatal) transmission (1%-2%) in the United States, which has been made possible by effective public health interventions (eg, universal HIV testing, preconception counseling, family planning) and medical interventions (eg, antiretroviral therapy, preexposure prophylaxis). 20 In contrast to earlier work suggesting that HIV posed a challenge for reproduction, recent studies have revealed that HIV-positive status does not diminish women's desire to bear children but rather is one of many factors considered in reproductive preferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation